Darwin, dharma, and the divine : evolutionary theory and religion in modern Japan - Godart, G. Clinton (Studies of the Weatherhead East Asian Institute, Columbia University., 2017)
'Darwin, Dharma, and the Divine' demonstrates that evolutionary theory was never passively accepted, but played active and controversial roles in modern Japanese thought.